Mixed Linearity Improvement Techniques for Ultra-wideband Low Noise Amplifier - Mohammed Nadhim Abbas; Farooq Abdulghafoor Khaleel (Institute of Advanced Engineering and Science, 2018)
We present the linearization of an ultra-wideband low noise amplifier (UWB-LNA) operating from 2GHz to 11GHz through combining two linearization methods. The used linearization techniques are the combination of post-distortion cancellation and derivative-superposition linearization methods. The linearized UWB-LNA shows an improved linearity (IIP3) of +12dBm, a minimum noise figure (NFmin.) of 3.6dB, input and output insertion losses (S11 and S22) below -9dB over the entire working bandwidth, midband gain of 6dB at 5.8GHz, and overall circuit power consumption of 24mW supplied from a 1.5V voltage source. Both UWB-LNA and linearized UWB-LNA designs are verified and simulated with ADS2016.01 software using BSIM3v3 TSMC 180nm CMOS model files. In addition, the linearized UWB-LNA performance is compared with other recent state-of-the-art LNAs.